A preliminary investigation on improving functional communication training by mitigating resurgence of destructive behavior. Issue 4 (23rd July 2016) - Fuhrman, Ashley M.; Fisher, Wayne W.; Greer, Brian D.
Abstract : Despite the effectiveness and widespread use of functional communication training (FCT), resurgence of destructive behavior can occur if the functional communication response (FCR) contacts a challenge, such as lapses in treatment integrity. We evaluated a method to mitigate resurgence by conducting FCT using a multiple schedule of reinforcement prior to extinction. After functional analyses of 2 boys' destructive behavior and treatment with FCT (Study 1), we compared levels of resurgence during an extinction challenge either after a typical FCT sequence or after exposure to schedule thinning in the context of a multiple‐schedule arrangement (Study 2). Results for both participants suggested that schedule thinning using discriminative stimuli in a multiple schedule mitigated the resurgence of destructive behavior.